Identification of Small RNAs During High Light Acclimation in Arabidopsis thaliana - Tiwari, Bhavika; Habermann, Kristin; Arif, M. Asif; Top, Oguz; Frank, Wolfgang (Frontiers in Plant Science, 2021)
The biological significance of non–coding RNAs (ncRNAs) has been firmly established to be important for the regulation of genes involved in stress acclimation. Light plays an important role for the growth of plants providing the energy for photosynthesis; however, excessive light conditions can also cause substantial defects. Small RNAs (sRNAs) are a class of non-coding RNAs that regulate transcript levels of protein-coding genes and mediate epigenetic silencing. Next generation sequencing facilitates the identification of small non-coding RNA classes such as miRNAs (microRNAs) and small-interfering RNAs (siRNAs), and long non-coding RNAs (lncRNAs), but changes in the ncRNA transcriptome in response to high light are poorly understood. We subjected Arabidopsis plants to high light conditions and performed a temporal in-depth study of the transcriptome data after 3 h, 6 h and 2 d of high light treatment. We identified a large number of high light responsive miRNAs and sRNAs derived from NAT gene pairs, lncRNAs and TAS transcripts. We performed target predictions for differentially expressed miRNAs and correlated their expression levels through mRNA sequencing data. GO analysis of the targets revealed an overrepresentation of genes involved in transcriptional regulation. In A. thaliana, sRNA-mediated regulation of gene expression in response to high light treatment is mainly carried out by miRNAs and sRNAs derived from NAT gene pairs, and from lncRNAs. This study provides a deeper understanding of sRNA-dependent regulatory networks in high light acclimation.